Acidic Urine Is Associated With Poor Prognosis of Upper Tract Urothelial Carcinoma - Han, Jang Hee; Jeong, Seung-hwan; Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon (Frontiers in Oncology, 2022)
Purpose To assess the prognostic role of acidic urine (low urine pH) in upper tract urothelial cancer (UTUC). Materials and Methods We reviewed patients enrolled in Seoul National University Prospectively Enrolled Registry for Urothelial Cancer-Upper Tract Urothelial Cancer (SUPER-UC-UTUC) who underwent surgical resection from March 2016 to December 2020 in Seoul National University Hospital (SNUH). Patients with non-urothelial cancer or those who are in condition at end-stage renal disease were excluded. Acidic urine was defined as urine pH ≤ 5.5. Results A total of 293 patients with a mean age of 70.7 ± 9.5 years were enrolled in this study. Pre-operative laboratory results showed a mean estimated glomerular filtration rate (eGFR) of 64.1 ± 19.2 mL/min/1.73m2 and a mean urine pH of 5.86 ± 0.66. Patients were subdivided into low (pH ≤ 5.5) and high (pH > 5.5) urine pH for comparison. As a result, all variables were comparable except for the T stage, which was significantly higher in the low urine pH group (p = 0.017). Cox regression analysis was performed to assess the clinical impact of acidic urine on patient survival. Multivariate Cox regression analysis revealed that tumor multifocality (HR 2.07, p = 0.015), higher T stage (HR 1.54, p = 0.036), lymphovascular invasion (HR 1.69, p = 0.033), eGFR < 60 mL/min per 1.73 m2 (HR 1.56, p = 0.017), and acidic urine (HR 1.63, p < 0.01) independently decreased disease-free survival (DFS), while multifocality (HR 9.50, p < 0.01), higher T stage (HR 9.51, p = 0.001) and acidic urine (HR 10.36, p = 0.004) independently reduced the overall survival (OS). Conclusions Acidic urine is independently associated with reduced DFS and OS in UTUC. Acidic urine contributing to acidic environment may promote acquisition of agressive behavior of UTUC.